Liquid phase conversion optical metamaterial perfect absorber and preparation method thereof
The light absorbing layer of high-temperature metamaterials is prepared by liquid phase conversion solution and nanoimprinting method, which solves the problems of process compatibility, material selection and preparation methods in the prior art, and achieves the effects of efficient light absorption and high temperature stability.
Patent Information
- Application Number
- CN202411698980.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing high-temperature metamaterial perfect absorbers have many problems in process compatibility, material selection and preparation methods, which lead to limited promotion and popularization in practical applications.
The light absorbing layer was prepared by a liquid phase conversion solution combined with sol-gel method and nanoimprinting method. The inorganic ceramic light absorbing layer was obtained by pyrolysis to achieve the formation of microstructures and efficient absorption of light energy.
Improve process compatibility and preparation flexibility, reduce production costs, and achieve efficient light absorption and physical and chemical stability in high-temperature environments.
Smart Images

Figure CN119529765A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy conversion, and in particular relates to a liquid phase transformed optical metamaterial perfect absorber and a preparation method thereof. Background Art
[0002] The basic principle of the perfect absorber is to achieve efficient absorption of light radiation through specially designed microstructures and material properties, convert light energy into heat energy, and control the release of thermal radiation through narrow-band selective emission. It exhibits high absorptivity in a wide spectrum (such as 0.3 to 2.5 μm), can significantly reduce reflection losses, and is suitable for application in high-efficiency energy conversion fields such as solar thermal photovoltaic (STPV) systems, industrial waste heat recovery, and spacecraft thermal management. In the STPV system, the perfect absorber can effectively absorb solar radiation and convert it into heat energy, which is further converted into electrical energy through thermophotovoltaic cells, thereby improving the utilization efficiency of solar energy; it also plays a key role in industrial waste heat recovery and thermal protection of aerospace equipment, which can reduce the energy loss of equipment and extend its service life.
[0003] High-temperature metamaterial perfect absorbers face many problems in current technology: first, the process compatibility is poor, and it is difficult to prepare microstructure layers on semiconductor chips with traditional ceramic materials; second, the material selection is limited, mainly relying on high-cost precious metals or special ceramics; third, the preparation method is complex and expensive, and the manufacturing cycle is long and costly. These problems directly affect the promotion and popularization of perfect absorbers in practical applications. It is difficult to prepare microstructure layers on semiconductor chips with traditional ceramic materials, which makes the integration of multilayer structures challenging. Chen Shuangjun et al. pointed out in their study that it is difficult for traditional ceramic materials to directly form microstructure layers on the chip surface due to pyrolysis requirements and material incompatibility. Secondly, the limited material selection affects the performance of high-temperature absorbers. Many studies rely on high-melting-point metals such as tungsten and molybdenum. Although these materials perform well at high temperatures, their high cost limits the feasibility of large-scale applications. Daniel et al. pointed out in their study that although tungsten has good thermal stability as an absorber material, its production cost is too high, which limits its practical application. The complexity and costliness of the preparation method make many high-performance absorbers difficult to achieve in the industrial process. Wang Jie mentioned in his research that although magnetron sputtering can produce highly selective absorption coatings, its complex process, high production cost and low efficiency restrict its large-scale application. Summary of the invention
[0004] The purpose of the present invention is to provide a liquid phase transformation optical metamaterial perfect absorber and a preparation method thereof, wherein a light absorbing layer is prepared by liquid phase transformation ceramics, a microstructure is formed on the light absorbing layer by a sol-gel method and a nanoimprint method, and then an inorganic ceramic light absorbing layer is obtained by pyrolysis. The light absorbing layer has good process compatibility and preparation flexibility, and also has the advantages of simple preparation process and low production cost.
[0005] The technical solution of the present invention is as follows:
[0006] A liquid phase transformation optical metamaterial perfect absorber, which includes a substrate, an insulating layer and a light absorbing layer from bottom to top, wherein the light absorbing layer is a ceramic film with a plurality of microstructures;
[0007] The light absorbing layer is obtained by forming a sol film with several microstructures from a liquid phase conversion solution through a solution-gel method and a nanoimprint method and then pyrolyzing the film at 700-1000°C;
[0008] The liquid phase conversion solution includes a doping phase and a polymer ceramic precursor, the doping phase is at least one of carbon nanotubes, graphene, silicon carbide, titanium carbide, silicon nitride, boron nitride, indium tin oxide and zirconium oxide, and the polymer ceramic precursor is a silicon-based precursor;
[0009] The addition amount of the doping phase is 35-70wt% of the solid content in the liquid phase conversion solution, and the average particle size of the doping phase is 1nm-100μm.
[0010] In some possible implementations, the microstructure is at least one of a pyramid structure, an inverted pyramid structure, and a nano-pillar array structure.
[0011] In some possible implementations, the doped phase is indium tin oxide, and the polymer ceramic precursor is polysilazane.
[0012] In some possible implementations, the adhesion strength between the substrate and the insulating layer, and between the insulating layer and the light absorbing layer is greater than 6.65 MPa.
[0013] In some possible implementations, the thickness of the light absorbing layer is 500 nm-10 μm, and the thickness of the insulating layer is 10-200 μm.
[0014] In some possible implementations, the insulating layer is made of a high-temperature insulating material, and the high-temperature insulating material includes at least one of aluminum oxide, magnesium oxide, boron nitride, and silicon oxide.
[0015] In some possible implementations, the substrate is a metal substrate. Preferably, the substrate is a nickel-based alloy substrate, a stainless steel substrate or a tungsten substrate.
[0016] A method for preparing the above optical metamaterial perfect absorber comprises the following steps:
[0017] (1) ultrasonically clean the substrate and then dry it;
[0018] (2) Spin coating or high temperature coating a high temperature insulating material on the substrate, curing and cross-linking at 100-200° C. for 30-60 min, then heating to 800-1000° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 1-2 h to obtain an insulating layer;
[0019] (3) mixing the doping phase and the polymer ceramic precursor in proportion and dispersing them in an organic solvent, and obtaining a uniformly mixed and bubble-free liquid phase conversion solution after magnetic stirring and ultrasonic treatment;
[0020] (4) The phase inversion solution is spin-coated on the insulating layer and then dried at 60-100° C. to obtain a sol film.
[0021] (5) placing the sol film in a mold with a microstructure, and imprinting the microstructure on the surface of the sol film by nanoimprinting technology at a temperature of 100 to 200° C., and finally pyrolyzing the sol film imprinted with the microstructure at 700 to 1000° C. for 1 h.
[0022] In some possible implementations, the mold is made of silicon or metal.
[0023] In some possible implementations, the organic solvent in step (3) is acetone.
[0024] The present invention has at least the following beneficial effects:
[0025] The light absorbing layer of the optical metamaterial perfect absorber provided by the present invention is prepared by a liquid phase conversion solution combined with a sol-gel method and a nanoimprint method. The liquid phase conversion solution used significantly improves the process compatibility and can be coated on different substrates by a sol-gel method or a coating method at low temperatures, having good process compatibility and preparation flexibility. At the same time, the solution gel method and micro-nano patterning technology (nanoimprint method) are used to effectively reduce production costs and have high industrial adaptability.
[0026] In addition, the liquid phase conversion solution includes a polymer ceramic precursor and a doping phase. Through the formulation and pyrolysis process of the liquid phase conversion solution, the liquid phase conversion ceramic can achieve structural design from micrometer to nanometer level, thereby improving the light capture efficiency of the absorber. Specifically, the microstructure set on the surface of the light absorbing layer can effectively increase the multiple reflection paths of light, improve its light absorption rate and light capture efficiency.
[0027] Finally, the doping phase in the liquid phase conversion solution as a high temperature durability component can enhance the oxidation resistance and thermal stability of the absorber in a high temperature environment, so that the optical metamaterial perfect absorber can maintain good physical and chemical stability and excellent oxidation resistance at high temperatures, and adapt to high temperature environments above 1000°C. This is crucial for high temperature applications such as solar thermal photovoltaic systems (STPV) and industrial waste heat recovery. The liquid phase conversion solution avoids the common structural degradation problem during pyrolysis by converting the polymer precursor into a ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of Example 1 of the present invention;
[0029] Figure 2 The film layer structure of a liquid phase transformed optical metamaterial perfect absorber according to Example 1 of the present invention;
[0030] Figure 3 Schematic diagram of the microstructure of the light absorbing layer of Example 1 of the present invention;
[0031] Figure 4 is the incident rate of light on the perfect absorber of the optical metamaterial of the present invention;
[0032] Figure 5 is the light transmittance of the perfect absorber of the optical metamaterial of the present invention.
[0033] Reference numerals in the figure: 1-substrate, 2-insulating layer, 3-light absorbing layer. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0035] In the following examples, the water used can be one or more of distilled water, purified water, and drinking water; unless otherwise specified, the detection methods in the following examples are conventional detection methods; the reagents in the following examples are purchased from commercial channels unless otherwise specified.
[0036] Example 1
[0037] A method for preparing an optical metamaterial perfect absorber, such as Figure 1 As shown, the following steps are included:
[0038] (1) The nickel-based alloy substrate was cleaned with acetone, alcohol, and deionized water in sequence, ultrasonicated for 5 min in sequence, and placed in a vacuum drying oven to dry the substrate.
[0039] (2) Alumina insulating slurry was spin-coated on the substrate by screen printing, and the substrate was placed on a heating table and heated to 200°C for half an hour to cure and cross-link. The substrate was then placed in a tubular furnace and heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 1 hour for high temperature annealing. The thickness of the insulating layer was 100 μm.
[0040] (3) Polysilazane, indium tin oxide (ITO) with a particle size of 50 μm, and acetone are mixed in a mass ratio of 1:4:2, and a uniformly mixed liquid phase conversion solution without bubbles is obtained after magnetic stirring and ultrasound.
[0041] (4) The liquid phase conversion solution obtained in step (3) is spin-coated on the insulating layer by screen printing, and then placed in an oven at 60° C. for drying to remove the solvent and ensure uniform solidification of the film layer, thereby obtaining a sol film with a thickness of 5 μm.
[0042] (5) Prepare a mold with a pyramid-shaped microstructure, the mold is made of silicon material. Then, the sol film prepared in step (4) is closely contacted with the mold, and the pyramid-shaped micro-nanostructure is imprinted onto the film surface by high pressure heating. The imprinting process is carried out at a temperature of 200°C, and the imprinted sol film with a microstructure is placed in a tube furnace for pyrolysis to obtain Figure 2 and Figure 3 The optical metamaterial perfect absorber is shown, where the sintering temperature is 1000°C and the sintering time is 1 h.
[0043] Example 2
[0044] A method for preparing an optical metamaterial perfect absorber comprises the following steps:
[0045] (1) The stainless steel substrate was cleaned with acetone, alcohol, and deionized water in sequence, ultrasonicated for 5 min, and placed in a vacuum drying oven to dry the substrate.
[0046] (2) Alumina insulating slurry was spin-coated on the substrate by screen printing, and the substrate was placed on a heating table and heated to 200°C for curing and cross-linking for half an hour to obtain an insulating layer. The insulating layer was heat-treated and placed in a tubular furnace for heating at a rate of 10°C / min to 1000°C and kept at this temperature for 2 hours for high-temperature annealing. The thickness of the insulating layer was 100 μm.
[0047] (3) Polysilazane, indium tin oxide with a particle size of 50 μm, and acetone are mixed in a mass ratio of 1:4:2, and a uniformly mixed liquid phase conversion solution without bubbles is obtained after magnetic stirring and ultrasound.
[0048] (4) The liquid phase conversion solution obtained in step (3) is spin-coated on the insulating layer by screen printing, and then placed in an oven at 60° C. for drying to remove the solvent and ensure uniform solidification of the film layer, thereby obtaining a sol film with a thickness of 5 μm.
[0049] (5) Prepare a mold with a pyramid-shaped microstructure, the mold is made of silicon material. Then, the sol film prepared in step (4) is closely contacted with the mold, and the pyramid-shaped micro-nanostructure is imprinted onto the surface of the film by high-pressure heating. The imprinting process is carried out at a temperature of 200° C. The imprinted sol film with the microstructure is placed in a tubular furnace for pyrolysis, the sintering temperature is 1000° C., and the sintering time is 1 hour.
[0050] Example 3
[0051] A method for preparing an optical metamaterial perfect absorber comprises the following steps:
[0052] (1) cleaning the nickel-based alloy substrate with acetone, alcohol, and deionized water in sequence, ultrasonicating the substrate for 5 minutes in sequence, and placing the substrate in a vacuum drying oven to dry the substrate;
[0053] (2) Deposit an aluminum oxide thin film insulating layer on the substrate by chemical vapor deposition, depositing it step by step to a total thickness of 100 μm, with 10-20 μm deposited each time. After each deposition, place it on a heating table and heat it to 200°C, and cure and cross-link it for 30 minutes to ensure the uniformity and initial strength of the film layer. Then, the deposited insulating layer is subjected to high-temperature annealing, placed in a tube furnace for heating at a rate of 3°C / min, heated to 800°C, and kept warm for 1 hour.
[0054] (3) Polysilazane, indium tin oxide with a particle size of 50 μm, and acetone are mixed in a mass ratio of 1:4:2, and a uniformly mixed liquid phase conversion solution without bubbles is obtained after magnetic stirring and ultrasound.
[0055] (4) The liquid phase conversion solution obtained in step (3) is spin-coated on the insulating layer by screen printing, and then placed in an oven at 60° C. for drying to remove the solvent and ensure uniform solidification of the film layer, thereby obtaining a sol film with a thickness of 5 μm.
[0056] (5) Prepare a mold with a pyramid-shaped microstructure, the mold is made of silicon material. Then, the sol film prepared in step (4) is closely contacted with the mold, and the pyramid-shaped micro-nanostructure is imprinted onto the surface of the film by high-pressure heating. The imprinting process is carried out at a temperature of 200° C. The imprinted sol film with the microstructure is placed in a tubular furnace for pyrolysis, the sintering temperature is 1000° C., and the sintering time is 1 hour.
[0057] Example 4
[0058] The optical metamaterial perfect absorber prepared in Example 1 was tested for light absorption rate, and the calculation formula of light absorption rate was: light absorption rate = 1 - incidence rate - transmittance.
[0059] The incident light and transmittance were tested using a spectrophotometer. The sample was placed in the light path using an integrating sphere accessory. The reflected light from the sample surface was captured to obtain the reflected light intensity at each wavelength. Figure 4 , which is the incident light intensity of the liquid phase conversion ceramics without ITO and with different proportions of ITO in the target wavelength range. Make sure that the incident light is completely captured by the integrating sphere to obtain the true value of the reflection. Place the sample in the light path and measure the light intensity passing through the sample. Adjust the wavelength setting of the spectrophotometer, scan the target wavelength range (800nm-2500nm), and obtain the transmitted light at each wavelength, such as Figure 5 , is the comparison of the transmitted light intensity of the liquid phase conversion ceramics without and doped with different proportions of ITO in the target wavelength range. It can be seen that efficient light absorption can be achieved in a wide spectral range.
[0060] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A liquid phase transformation optical metamaterial perfect absorber, which comprises a substrate, an insulating layer and a light absorbing layer from bottom to top, characterized in that: The light absorbing layer is a ceramic film having a plurality of microstructures; The light absorbing layer is obtained by forming a sol film having a plurality of microstructures from a liquid phase conversion solution through a solution-gel method and a nanoimprint method and then pyrolyzing the film at 700-1000° C.; Wherein, the liquid phase conversion solution comprises a doping phase and a polymer ceramic precursor, the doping phase is at least one of carbon nanotubes, graphene, silicon carbide, titanium carbide, silicon nitride, boron nitride, indium tin oxide and zirconium oxide, and the polymer ceramic precursor is a silicon-based precursor; The addition amount of the doping phase is 35-70wt% of the solid content in the liquid phase conversion solution, and the average particle size of the doping phase is 1nm-100μm.
2. The optical metamaterial perfect absorber according to claim 1, characterized in that: The microstructure is at least one of a pyramid structure, an inverted pyramid structure and a nano-column array structure.
3. The optical metamaterial perfect absorber according to claim 1 or 2, characterized in that: The doping phase is indium tin oxide, and the polymer ceramic precursor is polysilazane.
4. The optical metamaterial perfect absorber according to claim 1, characterized in that: The adhesion strength between the substrate and the insulating layer, and between the insulating layer and the light absorbing layer are both greater than 6.65 MPa.
5. The optical metamaterial perfect absorber according to claim 1, characterized in that: The thickness of the light absorbing layer is 500nm-10μm, and the thickness of the insulating layer is 10-200μm.
6. The optical metamaterial perfect absorber according to claim 1, characterized in that: The insulating layer is made of a high temperature insulating material, and the high temperature insulating material includes at least one of aluminum oxide, magnesium oxide, boron nitride and silicon oxide.
7. The optical metamaterial perfect absorber according to claim 1, characterized in that: The substrate is a metal substrate.
8. The optical metamaterial perfect absorber according to claim 7, characterized in that: The substrate is a nickel-based alloy substrate, a stainless steel substrate or a tungsten substrate.
9. A method for preparing an optical metamaterial perfect absorber according to any one of claims 1 to 7, characterized in that: The steps include: (1) ultrasonically clean the substrate and then dry it; (2) spin coating or high temperature coating a high temperature insulating material on the substrate, curing and cross-linking at 100-200° C. for 30-60 min, then heating to 800-1000° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 1-2 h to obtain an insulating layer; (3) mixing the doping phase and the polymer ceramic precursor in proportion and dispersing them in an organic solvent, and obtaining a uniformly mixed and bubble-free liquid phase conversion solution after magnetic stirring and ultrasonic treatment; (4) spin coating the phase inversion solution on the insulating layer, and then drying at 60-100° C. to obtain a sol film; (5) placing the sol film in a mold with a microstructure, and imprinting the microstructure on the surface of the sol film by nanoimprinting technology, the imprinting temperature is 100-200° C., and finally pyrolyzing the sol film imprinted with the microstructure at 700-1000° C. for 1-3 h.
10. The preparation method according to claim 9, characterized in that: The mold is made of silicon or metal.
Citation Information
Patent Citations
Method for the production of thin layers of metal-ceramic composite materials
CN101600915A
Broadband perfect absorber based on metallic film-core shell plasma structure
CN108919391A
Perfect optical absorber with dual differential response of polarization adjustable spectrum and preparation method thereof
CN110687622A
Ceramic coating having functional micro / nano structure on surface thereof and preparation method therefor
CN110958994A
Thermo-electron optical detector based on perfect absorption metamaterial and preparation method thereof
CN111477700A